"Healthcare seems to vary a lot": A focus group study among parents of children with severe allergy. (9th August 2017) - Lagercrantz, Birgitta; Persson, Åsa; Kull, Inger
ABSTRACT: Background : Living with an allergic disease has consequences for both affected children and their families. The aim of this qualitative study was to gain deeper knowledge of what life is like for families of children with severe allergic disease, in order to improve care and thereby reduce the consequences of living with a chronic disease. Methods : Four focus group interviews were performed with Swedish parents of children, aged 6–11 and 12–16 years, with severe allergic disease (from one or more allergic conditions, such as food allergy/eczema/hay fever/asthma). The participants were attending a family support weekend. Interviews were analyzed with a qualitative method. Results : Based on parental experiences, the following themes were presented in the analysis: limitations, control, injustices, and fear and anxiety . It was evident that the families lived isolated lives and experienced different kinds of limitations. Parents felt a need to have control of their child's everyday life and described a feeling of constantly being on guard. They also suggested that understanding of the child's allergies was lacking in preschool/school and that healthcare did not provide adequate support. They felt that the same care should be offered to children and families, no matter where they lived. Conclusions : Based on parental experiences, having a child with severe allergic disease implies a need to constantly be on guard. In order to improve the care of children with severe allergy and their families, a more person- and family-centered approach is needed.